Seaweed responses to ocean acidification: global impacts on growth, biochemical composition, and CO2 mitigation potential - I. Eswar; Abantika Majumder; Suhail Haq Raja mohamed; K. Logesh; Shek Mohamed Ibrahim Shek alavudeen; M. Hariprakash; Dinesh Kumar Sundarraj (Discover Oceans)
Abstract Ocean acidification, driven by the absorption of elevated atmospheric CO2 levels, significantly affecting the growth and nutritional composition of marine biota, including seaweeds. The increasing expansion of the cultivation of seaweed is a promising method for removing carbon dioxide through both government and private sectors. There are notable comprehensive assessments that evaluated the effectiveness of seaweed farming to achieve significant climate change mitigation and it ended with positive outcome. Hence the present article reviews about the global impacts of ocean acidification on seaweed communities including growth dynamics, nutritional trends, and their potential for CO2 mitigation. The ecological consequences of ocean acidification and providing an overview of its status. Amplified CO2 levels affect seaweed physiology and ecosystem dynamics that have an influence on biodiversity, carbon cycling, and nutrient flows. The review highlights the trends in seaweed growth under elevated CO2 conditions, through identification of both opportunities and challenges for maintenance of productivity and nutritional quality. Seaweeds exhibit potential for CO2 sequestration, that whorls to offset carbon emissions through aquaculture practices. Furthermore, integrated seaweed farming practices can enhance environmental benefits, such as biodiversity conservation, nutrient remediation, and improved carbon storage. Finally, yet importantly this article emphasizes the necessity for targeted research that aimed at optimization of seaweed cultivation techniques, decipher species-specific responses to ocean acidification, and leveraging biotechnological advancements for maximation in mitigation of CO2. The findings underscore the role of seaweed aquaculture as a sustainable strategy to combat climate change and protect marine ecosystems.